(untitled) (Journal of Oriental Studies, 2023)
In this article, for the first time, information about the genealogies of the descendants of Chagatai, the son of Genghis Khan, from a Turkic-language source of the 16th century is introduced into scientific circulation. The name of this source is Tavarikhi Guzidayi Nusrat-name. This source was written with the active participation of Muhammad Sheibani, or was written by Muhammad Sheibani himself. In 1969, within the framework of the collection MHKK (materials on the history of the Kazakh Khanates), the genealogies of the Jochids from the Leningrad copy of this primary source were published. As part of the «Cultural Heritage» program, this translation was republished. The London copy was not available to researchers for a long time. In 2022, a Turkish translation of the London copy of Tavariha Guzidayi Nusratname was published. Also, the London copy of Tawarikh Guzidayi Nusrat-name became available online in a good quality. The purpose of our article is to introduce into scientific circulation the scientific translation of this source. Given the synchronism of writing this source with the lifetime of many Chagatayid rulers, it can be argued that this source, along with Jami at-Tawarikh Rashid ad-Din and Muizz al Ansab, is one of the three most important sources on the genealogy of the Chagataids. The research methodology consists in translating this source into Russian. At the same time, scientific comments will be given using the comparative method. As a result of the analysis, we have identified new data on the genealogy of different branches of the Chagataids. After the introduction of this source into scientific circulation, we received new information about certain aspects of the life of the Chagataids, in particular regarding the 15th-16th centuries. The source was translated by A.A. Zhumabayeva. The rest of the article and comments on the translation were made by Zh.M. Sabitov. Key words: Tavarikhi Guzidayi-nusrat name, Genghisides, Genealogies of Genghisides, Chagataids, Moghulistan.